2019
DOI: 10.1016/s0140-6736(19)31145-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and recent trends in hypertension awareness, treatment, and control in 12 high-income countries: an analysis of 123 nationally representative surveys

Abstract: Summary Background Antihypertensive medicines are effective in reducing adverse cardiovascular events. Our aim was to compare hypertension awareness, treatment, and control, and how they have changed over time, in high-income countries. Methods We used data from people aged 40–79 years who participated in 123 national health examination surveys from 1976 to 2017 in 12 high-income countries: Australia, Canada, Finland, Germany, Ireland, Italy, Japan, New Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
232
11
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(260 citation statements)
references
References 39 publications
11
232
11
6
Order By: Relevance
“…16.5% in males and 34.1% in females [3]. In comparison, a study with data from 123 nationally representative surveys of 40-79 year olds in 12 high income countries [21] found that control in males ranged from 17% in Ireland to 69% in Canada. For females, from 26% in Ireland to 58% in Germany.…”
Section: Discussionmentioning
confidence: 91%
“…16.5% in males and 34.1% in females [3]. In comparison, a study with data from 123 nationally representative surveys of 40-79 year olds in 12 high income countries [21] found that control in males ranged from 17% in Ireland to 69% in Canada. For females, from 26% in Ireland to 58% in Germany.…”
Section: Discussionmentioning
confidence: 91%
“…These advantages of our results still exist when compared with recent survey data from other countries [16,17]. A retrospective analysis showed that the BP control rate of hypertension was 60.6% in the general practice in Italy in 2013 [18].…”
Section: Resultsmentioning
confidence: 47%
“…A retrospective analysis showed that the BP control rate of hypertension was 60.6% in the general practice in Italy in 2013 [18]. In the most recent surveys on high-income countries, their treatment rates were at most 80% and control rates were less than 70% [16]. Among them, Canada, the United States, South Korea and Germany have the highest control coverage, and they all have national hypertension education and health check-up, which is definitely important for management effect [16].…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies published in The Lancet on hypertension control in high-, middle-, and lowincome countries revealed an increasing trend of hypertension prevalence over time [53]. It is widely acknowledged that high BP is one of the most important risk factors for stroke and heart disease [54].…”
Section: Hypertensionmentioning
confidence: 99%